Improvement Of Organizational Economic Mechanisms Of Transformation Of Energy Resources Markets. - Egamberdiev Madaminbek Muhammadjonovich (Periodica Journal, 2024)
Economic management tools are understood as methods and ways of influencing the object of management with the help of a specific comparison of costs and results (material incentives and sanctions, financing and lending, wages, cost, profit, price). Under the organizational tools of enterprise management are understood methods and methods of direct influence, which are of a directive, mandatory nature, based on discipline, response-bility, power and coercion
Keywords: Market; balanced; coordinat; development